silver hair(?) (silver ear???); silver hairs (1974)
silver n Now 'fore now 'twas all white foxes; that's what we call ice foxes, you know. But no ice foxes comes up now. Never see ne'er one. 'Tis all dark foxes now, red an' r silver hairs(?) an' . (sounds like name for type of fox rather than just designating a particular colour of fur) Yes DNE-cit DNE-cit J.D.A.WIDDOWSON APR 1974 Used I and Sup Used I 2 Used I ~ fir/fox/hair (fox)/jar/thaw/ patch fox, GLITTER, PATCH FOX. The source is listed as T 391/3-67 in DNE.The card is stamped twice.